ANALISIS PENGGUNAAN MEDIA SOSIAL FACEBOOK TERHADAP PENENTUAN HARGA BATU MERAH DI DESA GENTUNGAN KABUPATEN GOWA - Andi Muhammad Lukman; Andi Syadaruddin; Muhammad Ardi; Amal Nur; Zulpriyadi Zulpriyadi (Universitas Ichsan Sidenreng Rappang, 2026)
The main objective of this study is to describe the phenomenon of Facebook becoming a strategic tool for local business actors to build product image, expand market networks, and strengthen the economic existence of the community. Promotion on Facebook provides a comprehensive communication impact, consumers obtain new information about products, prices, and quality of red stone through visual and descriptive content. The results of the study show that people as red stone craftsmen think they open Facebook more than once a day as many as 70 (47%) of 150 respondents. People who think they open Facebook every day as many as 44 (29%). People who disagree as many as 28 (19%), and those who strongly disagree as many as 8 (5%). People often use Facebook to search for product information as many as 76%. Red stone craftsmen think that using Facebook to search for the latest news and information as many as 77 people or 51%, and often use Facebook to promote red stone products as many as 79 (53%). There are 87 people or 58% who think that promotion through Facebook can increase sales of red stone products.